Integration of science and religion in general courses: Insights from Islamic teacher education - Jaeni, Muhamad; Kusumawati, Putri Rahadian Dyah (Asatiza: Jurnal Pendidikan, 2025)
This study investigates lecturers’ understanding of the concept and approaches to integrating general and religious sciences within the Madrasah Ibtidaiyah Teacher Education program. The integration of science and religion is a critical aspect of the curriculum, as the program aims to prepare future educators capable of teaching scientific concepts imbued with religious values in a holistic manner, thereby eliminating the dichotomy between science and religion. This research employs a descriptive case study design with a qualitative approach. Data were collected through observation, documentation, and interviews, and analyzed using content analysis and descriptive analysis techniques. The findings reveal that lecturers' understanding of the integration of general and religious sciences can be categorized into two perspectives: (1) pragmatic understanding and (2) normative understanding. Furthermore, three distinct pedagogical approaches are employed to integrate these domains: (1) the equality approach, (2) the parallelization approach, and (3) the complementary approach. These findings provide valuable insights and serve as a foundation for policy development in Islamic higher education institutions, emphasizing their unique identity and contribution to education.